Intracytoplasmic sperm injection outcomes with cryopreserved testicular sperm aspiration samples. (22nd May 2015) - Roque, M.; Valle, M.; Marques, F.; Sampaio, M.; Geber, S.
Summary: Intracytoplasmic sperm injection (ICSI) may be performed with testicular frozen–thawed spermatozoa in patients with nonobstructive azoospermia (NOA). Sperm retrieval can be performed in advance of oocyte aspiration, as it may avoid the possibility of no recovery of spermatozoa on the day of oocyte pickup. There are few studies available in the literature concerning the use of frozen–thawed spermatozoa obtained from testicular sperm aspiration (TESA). To evaluate the effects and the outcomes of ICSI with frozen–thawed spermatozoa obtained by TESA, we performed a retrospective analysis of 43 ICSI cycles using frozen–thawed TESA. We obtained acceptable results with a fertilisation rate of 67.9%, an implantation rate (IR) of 17.1%, and clinical and ongoing pregnancy rates of 41.9% and 37.2% respectively. The results of this study suggest that performing ICSI using cryopreserved frozen–thawed testicular spermatozoa with TESA as a first option is a viable, safe, economic and effective method for patients with NOA.